The Implementation Of Multimedia Learning On Elementary Students’ Achievement In English Alphabet At Sd Negeri 062 Mompang Jae - Riski Rahmadani Nasution; Muhammad Sobri; Wulandari Lubis; Rini Azizah (Advances In Education Journal, 2025)
The rapid development of educational technology in the 21st century has transformed English language teaching, particularly through the integration of multimedia learning. This study aims to describe the implementation of multimedia learning in teaching the English alphabet and to analyze its influence on elementary students’ achievement at SD Negeri 062 Mompang Jae. This research employed a qualitative descriptive approach. The data were collected through classroom observations, interviews with teachers and students, and document analysis. The multimedia used included videos, songs, animated PowerPoint slides, and interactive games. The findings reveal that multimedia learning was implemented through visual and auditory activities that supported letter recognition, pronunciation, and writing skills. The use of multimedia increased students’ motivation, participation, and understanding of the English alphabet. However, several challenges were also identified, such as limited technological facilities and teachers’ lack of technical skills. Overall, multimedia learning contributed positively to students’ achievement when implemented appropriately. This study provides insights into the use of multimedia in elementary English instruction, particularly in rural school contexts.